2016
DOI: 10.7812/tpp/15-028
|View full text |Cite
|
Sign up to set email alerts
|

Population Variations in Rheumatoid Arthritis Treatment and Outcomes, Northern California, 1998–2009

Abstract: Objective: To assess variations in rheumatoid arthritis treatment and outcomes at the community level from 1998 through 2009. Methods:The study used computerized data from 16 Kaiser Permanente Northern California Medical Centers. Mixed modeling was used to assess patterns across time and clinic. The analysis accounted for patient demographics, clustering of patients within Medical Centers, and repeated measures of patients over time. The metric used to measure drug use, months of use per patient per year, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…When analyzing 1996–2009 computerized health care data from Kaiser Permanente Northern California, Curtis and colleagues reported a point prevalence of AS standardized to the 2000 US census of 2.26 per 1000 (~ 0.23%) [8]. These findings were higher than the rates reported during our study, but lower than previously reported prevalence rates in the U.S. For example, based on the 2009–2010 NHANES data, axSpA (AS and nr-axSpA) prevalence was approximately 1.4% in the U.S. [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing 1996–2009 computerized health care data from Kaiser Permanente Northern California, Curtis and colleagues reported a point prevalence of AS standardized to the 2000 US census of 2.26 per 1000 (~ 0.23%) [8]. These findings were higher than the rates reported during our study, but lower than previously reported prevalence rates in the U.S. For example, based on the 2009–2010 NHANES data, axSpA (AS and nr-axSpA) prevalence was approximately 1.4% in the U.S. [7].…”
Section: Discussionmentioning
confidence: 99%
“…Since our study analyzed the diagnostic prevalence of AS patients by identifying patients with ICD-9 and/or ICD-10 codes, our findings could be an under-representation of the overall AS population. As reported by Curtis et al, using different case definitions based on the same ICD codes may lead to variation in the prevalence estimates [8]. Published reports have indicated a delay in diagnosis of up to 10 years for AS patients [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chu et al noted that ADA nonadherence among adult RA patients was associated with corticosteroid use [29]. In examining RA treatment trends, Herrinton et al noted that as use of DMARDs including biologics increased (from 38 to 63%) between 1998 and 2009, use of steroids decreased (from 23% to 15%) [30]. The cumulative findings of these studies suggest that implementation of medication therapy considered more effective in the treatment of RA, namely biologic DMARDs, is associated with reduced need for less effective co-therapies such as steroids.…”
Section: Discussionmentioning
confidence: 99%
“…The increased use of disease-modifying antirheumatic drugs (DMARDs) and the introduction of biologic DMARDs have resulted in a greater proportion of patients experiencing remission or lower disease activity status. 2,3 The increasing use of these agents has resulted in lower rates of progression of radiographic disease in a prospective observational study following patients for 10 years. 2 At present, it is not known whether the improvements in medical management of this disease can influence the rates of tendon rupture.…”
Section: Introductionmentioning
confidence: 99%